2015
DOI: 10.1177/1524838015620820
|View full text |Cite
|
Sign up to set email alerts
|

The Maltreatment–Offending Association: A Systematic Review of the Methodological Features of Prospective and Longitudinal Studies

Abstract: Although the association between childhood maltreatment and the subsequent development of offending behavior is well documented, the association does not necessarily reflect a causal relationship. This paper provides a systematic review of prospective and longitudinal studies using official records of maltreatment to gain insights into the extent to which methodological variations are likely to influence the conclusions drawn about the likely relationship between maltreatment and offending. Sixty-two original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 80 publications
2
38
0
Order By: Relevance
“…This is a retrospective population-based cohort study that used de-identi ed, individual-level information linked across multiple administrative datasets. The study design was informed by a systematic review of the methodological features of past studies relating to the maltreatment-offending association [24]. The study population comprised all Aboriginal children born in the NT between 1st January 1999 and 31st December 2006 with at least one record in any of the linked datasets at or after age 10 years.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…This is a retrospective population-based cohort study that used de-identi ed, individual-level information linked across multiple administrative datasets. The study design was informed by a systematic review of the methodological features of past studies relating to the maltreatment-offending association [24]. The study population comprised all Aboriginal children born in the NT between 1st January 1999 and 31st December 2006 with at least one record in any of the linked datasets at or after age 10 years.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…A further consideration in future research is the use of official records of maltreatment in contrast with self-reported maltreatment. The majority of longitudinal studies examining the maltreatment-offending association have used official records of abuse and neglect (Malvaso, Delfabbro, & Day, 2015). Limited to information collected by official agencies, these studies might thus underestimate associations with offending because not all children and young people who experience maltreatment are notified.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example, longitudinal research suggests maltreated children have an elevated risk for being 'Not in Employment, Education, or Training' (NEET) [1] and lower levels of educational attainment [2]. In addition, exposure to maltreatment has been shown to increase the likelihood of criminal behaviour [3], further exposure to victimisation [4,5], teenage parenthood [6], and is also associated with subsequent lower life satisfaction [7], loneliness [8], and poorer sleep quality [9]. Moreover, the relationship between childhood maltreatment and functional impairment appears to occur in a dose-response manner such that exposure to more forms of maltreatment confers greater risk of poor adult functioning [4,10].…”
Section: Introductionmentioning
confidence: 99%